1987
DOI: 10.2307/1591019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Membrane Proteins from Salmonella gallinarum for Prevention of Fowl Typhoid Infection in Chickens

Abstract: Outer membrane protein isolated from Salmonella gallinarum was examined at different concentrations with or without a mineral-oil adjuvant for its immunogenicity and protection against live challenge. A formalin-killed whole-cell bacterin of the same organism was used for comparison. The results suggested that membrane proteins from S. gallinarum give better protection than formalin-killed whole-cell bacterin. Addition of an oil adjuvant to the protein appeared to increase the efficiency of the vaccine. When p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
2
20
0
1
Order By: Relevance
“…In contrast, the protection produced by formalin-killed Salmonella harvested from either in vitro or in vivo conditions when used as vaccine candidate in chickens was found to be statistically insignificant. This is in agreement with other researchers who found that proteins (OMPs) gave better protection than formalin-killed bacteria [25]. For other organisms, such as S. Gallinarum and Pasteurella multocida, OMPs also give better protection than whole bacterins or sonicated cells [25,26].…”
Section: Salmonella Enteritidis' Vaccine Produces In Vitro and In Vivsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the protection produced by formalin-killed Salmonella harvested from either in vitro or in vivo conditions when used as vaccine candidate in chickens was found to be statistically insignificant. This is in agreement with other researchers who found that proteins (OMPs) gave better protection than formalin-killed bacteria [25]. For other organisms, such as S. Gallinarum and Pasteurella multocida, OMPs also give better protection than whole bacterins or sonicated cells [25,26].…”
Section: Salmonella Enteritidis' Vaccine Produces In Vitro and In Vivsupporting
confidence: 92%
“…This is in agreement with other researchers who found that proteins (OMPs) gave better protection than formalin-killed bacteria [25]. For other organisms, such as S. Gallinarum and Pasteurella multocida, OMPs also give better protection than whole bacterins or sonicated cells [25,26]. Immunization with Helicobacter whole-cell extracts or purified components also effectively prevented H. pylori infection in mice [27][28][29][30].…”
Section: Salmonella Enteritidis' Vaccine Produces In Vitro and In Vivsupporting
confidence: 91%
“…Among the immunised groups, the chickens vaccinated with the ghost plus Montanide ISA TM 70 VG showed higher survival rates compared to those from chickens vaccinated with the ghost alone. Until recently, very few efforts have been directed toward the production of safe and immunogenic inactivated vaccines against fowl typhoid (Bouzoubaa et al, 1987;Bouzoubaa et al, 1989;Chaudhari et al, 2012;Jawale et al, 2014;Jawale and Lee, 2014b). The results of the current study highlight further progress in the development of inactivated S. Gallinarum vaccines.…”
Section: Discussionmentioning
confidence: 72%
“…In Africa, it has been reported in many countries including Tanzania, Uganda (Okoj, 1993), Senegal (Arbelot et al, 1997), Nigeria (Sa'idu et al, 1994) and Morocco (Bouzoubaa et al, 1987). It is a septicaemic disease that affects primarily chicken and turkey, although natural infections in many other avian species have been reported (Wray et al, 1996;Shivaprasad, 1997).…”
Section: Introductionmentioning
confidence: 99%